2012
DOI: 10.1021/ma3019238
|View full text |Cite
|
Sign up to set email alerts
|

Pd/C as a Clean and Effective Heterogeneous Catalyst for C–C Couplings toward Highly Pure Semiconducting Polymers

Abstract: Conjugated polymers are the primary blocks for organic electronics. Traditionally, conjugated polymers synthesized via Suzuki, Heck, and Stille couplings are catalyzed by soluble homogeneous ligated palladiums, which suffer the contaminations of residual nano-palladium and phosphine impurity resulting from side reaction of aryl−aryl exchange. To overcome these drawbacks, a commercially available, clean, and ligand-free heterogeneous catalyst Pd/C for the C−C coupling polymerizations was developed in this work.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
65
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(66 citation statements)
references
References 51 publications
0
65
0
Order By: Relevance
“…Mostly acceptable values of 10 -100 ppm are utilized in many other synthetic applications and can also be suggested in organic electronics. As a representative example, the preparation of highly pure semiconducting polymers with a Pd content of only 34 ppm has been described [34].…”
Section: Catalyst Decomposition and Vendor-dependent Purity Of Metal mentioning
confidence: 99%
See 1 more Smart Citation
“…Mostly acceptable values of 10 -100 ppm are utilized in many other synthetic applications and can also be suggested in organic electronics. As a representative example, the preparation of highly pure semiconducting polymers with a Pd content of only 34 ppm has been described [34].…”
Section: Catalyst Decomposition and Vendor-dependent Purity Of Metal mentioning
confidence: 99%
“…A heterogeneous Pd/C catalyst was utilized in the synthesis of thiophene building blocks for organic electronics [39] and for the preparation of highly pure semiconducting polymers [34]. It was found that the supported Pd/C catalyst gives better selectivity and efficiency in the synthesis of desired products in comparison to common Pd catalysts.…”
Section: Environmental Concerns Catalyst Recycling and Cost-eflciencymentioning
confidence: 99%
“…[19] Polymerization was performed in a THF/water mixture as solvent, with addition of N-methylpyrrolidinone or dimethylformamide to stabilize the palladium center and with K 2 CO 3 as the base. Both polymers P16 and P17 have diketopyrrolopyrrole as the acceptor unit and carbazole as the donor.…”
Section: Suzuki-miyaura Cross-couplingmentioning
confidence: 99%
“…This reaction has become for decades a major methodological tool available to chemists to build molecular architectures especially based on a biaryl scaffold. The biaryl motif can be found in numerous natural products, agrochemicals, drugs, polymers, ligands and thus triggered the attention of the scientific community for a wide range of applications [2][3][4][5][6][7][8][9]. If the formation of a biphenyl motif belongs nowadays to a textbook knowledge, the past decade has witnessed spectacular innovations and improvements such as ligandless transformations [10], supported or nanostructured catalytic systems [11][12][13], performing additives [14,15], neat and/or aqueous conditions [2,13,15], MW activations [10] for example.…”
Section: Introductionmentioning
confidence: 99%